2014
DOI: 10.1093/ajh/hpt294
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Intake and Renal Outcomes: A Systematic Review

Abstract: Available, but limited, evidence supports an association between high sodium intake (> 4.6g/day) and adverse outcomes. However, the association with low intake (vs. moderate) is uncertain, with inconsistent findings from cohort studies. There is urgent need to clarify the long-term efficacy and safety of currently recommended low sodium intake in patients with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 29 publications
1
46
1
1
Order By: Relevance
“…Results did not differ in sensitivity analyses excluding high-risk groups such as those with hypertension, heart failure, diabetes mellitus, or CKD. Smyth et al 14 then performed a systematic review evaluating the relationship between sodium intake and kidney outcomes in individuals with and without CKD (n = 8,129). Their results showed that in individuals with CKD, there was an association between high sodium intake and decline in GFR, as well as an increase in proteinuria, whereas the association of low and usual sodium intake with outcomes did not differ.…”
Section: How Does This Study Compare With Prior Studies?mentioning
confidence: 99%
“…Results did not differ in sensitivity analyses excluding high-risk groups such as those with hypertension, heart failure, diabetes mellitus, or CKD. Smyth et al 14 then performed a systematic review evaluating the relationship between sodium intake and kidney outcomes in individuals with and without CKD (n = 8,129). Their results showed that in individuals with CKD, there was an association between high sodium intake and decline in GFR, as well as an increase in proteinuria, whereas the association of low and usual sodium intake with outcomes did not differ.…”
Section: How Does This Study Compare With Prior Studies?mentioning
confidence: 99%
“…The efficacy of severe fluid restriction (<1 l/day) with or without sodium restriction was evaluated in two RCTs, but neither study showed any benefit [71,72]. Another systematic review evaluating the effect of sodium restriction on renal outcomes in diverse populations also showed that there is reasonable evidence to support an association between high sodium intake (>4.6 g/day) and adverse renal outcomes, but not between low sodium intake and better renal outcomes [73]. It should be noted that sodium restriction appears to have competing effects on both the heart and the kidney, lowering blood pressure and activating the RAAS.…”
Section: Established Treatment Strategiesmentioning
confidence: 99%
“…Ako je ovaj mehanizam oštećen, viši krvni pritisak je potreban da održi ekskreciju natrijuma za dato op-terećenje natrijumom što rezultuje hroničnim povećanjem krvnog pritiska [33]. Hipertenzija predstavlja ravnotežu između unosa natrijuma i izlučivanja natrijuma preko bubrega što vodi poremećaju srednjeg arterijskog pritiska [34].…”
Section: Bubregom Uslovljena Hipertenzijaunclassified